2011
DOI: 10.1142/s0217590811004444
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of the Effect of Multimarket Contacts on Us Air Carriers' Pricing Behaviors

Abstract: A number of empirical studies have shown that multimarket contacts facilitate collusive behaviors between full-service carriers (FSCs) in the US airline industry. This paper empirically investigates the effects of multimarket contacts on air carriers' pricing behaviors and highlights those of low-cost carriers (LCCs) and FSCs as well as those among LCCs. Simultaneous demand and price (pseudo-supply) equations are estimated to derive these impacts of multimarket contacts in the top 30 air markets in the US mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Fu et al (2011) found that service-differentiation between FSAs and LCCs leads to the cartelized behavior of FSAs. Murakami and Asahi (2011) studied the effect of multimarket contact on LCCs and FSAs and found that LCCs keep their airfares low despite the fact that they frequently have market contact with each other. Zhang et al (2014) showed by estimating the Lernerindex function that Chinese FSAs had market power and that there existed hub-premiums in the Chinese airline market, but the existence of LCCs lowered their market power.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fu et al (2011) found that service-differentiation between FSAs and LCCs leads to the cartelized behavior of FSAs. Murakami and Asahi (2011) studied the effect of multimarket contact on LCCs and FSAs and found that LCCs keep their airfares low despite the fact that they frequently have market contact with each other. Zhang et al (2014) showed by estimating the Lernerindex function that Chinese FSAs had market power and that there existed hub-premiums in the Chinese airline market, but the existence of LCCs lowered their market power.…”
Section: Literature Reviewmentioning
confidence: 99%